Acceptance analysis F coconut Dast Flour as a substitution of wheat flour in churros production: Case study of generation Z in DKI Jakarta - Wiliyanto, Wiliyanto; Rosanto, Stephanie (Universitas Wiralodra, 2023)
Coconut dregs are an element that has many health benefits. It has a high fiber content, so that it can be used as a substitute for wheat flour. However, from the point of view of its utilization, coconut dreg has yet to be utilized correctly and is only used as food waste. This study aims to determine the success and acceptability of a churros product with coconut dregs flour as a substitute. This research was conducted experimentally, which consisted of making churros using different variations of coconut dreg flour substitution in a total of 5 samples, with sample system. This control system at did not experience coconut dreg flour substitution. One hundred panelists, generation Z in DKI Jakarta, passed this acceptance test. The results of the organoleptic test on churros products with sample D had a level of preference (91.50%) which showed that churros sample D was very acceptable to the analysis shows that sample D is the dominant sample in terms of taste, texture and color. This result is based on the percentage of taste (93%), texture (89%), and color (87.80%). It would be better if the next trial of coconut dregs flour used food waste.